'Pushing the Boundaries' versus Identifying the Boundaries: An Institutional Perspective on NPM Principles. Issue 3 (19th May 2017) - Luke, Belinda; Kearins, Kate; Verreynne, Martie‐Louise
Abstract : This paper considers the boundaries of new public management (NPM) principles in the context of the mandate for a commercial approach within a New Zealand state‐owned enterprise (SOE). Investigating a commercial approach to NPM through an institutional theory lens, the case study highlights complexities and potential conflict between structured NPM principles and the more complex reality. Analysis reveals blurred lines and boundaries have implications for public sector organisations such as SOEs, government and other stakeholders, where managers push the boundaries beyond the point where stakeholders are comfortable. Thus, a key challenge involves developing clearer institutional boundaries to balance freedoms with stakeholder acceptability. Abstract : This paper considers the boundaries of new public management principles through a case study on a New Zealand state‐owned enterprise (SOE). Blurred lines and boundaries are highlighted, with implications for public sector organisations such as SOEs, government and other stakeholders.